PENCEGAHAN PRAKTIK PROSTITUSI ONLINE MELALUI LEMBAGA SEKOLAH DAN KELUARGA - Listyani, Refti Handini (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2017)
Although various problems arise from the existence of prostitution, the fact that the closure of prostitution also raises new problems. Closure of conventional prostitution opens the possibility of creating online prostitution, ie prostitution by utilizing social media. The advantages of this prostitution are its wider geographic range and make it easier to avoid security. This paper discusses the prevention of online prostitution through family and school institutions. The problem is the limited knowledge of parents related to the internet, especially related to the issue of online prostitution. Limitations of knowledge about internet problems cannot be separated from the social background of parents who come from the bottom economy. The same is true of suburban schools, whose teachers have little knowledge of the internet and the limited funds to organize educational events about internet dangers. One way out is educational support from the government as well as institutions that focus on the problems of children and adolescents